2020
DOI: 10.21203/rs.3.rs-25384/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The worldwide contribution of medical students during the COVID-19 pandemic: quantitative and qualitative research

Abstract: Background One of the biggest concerns regarding the COVID-19 pandemic is the extreme demand for health care workers and health systems. Medical students possess a range of skills and attributes that can help the declining workforce. This paper aims to provide an overview of the roles medical students have taken during this pandemic worldwide and provide insights to work towards establishing safe, efficient and useful roles during the progression of the pandemic. Methods A comprehensive questionnaire was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Nevertheless, as access to PPE and supervision improve, their contribution could be restricted to low-acuity COVID-19 patients [3]. This includes working in screening and assessment clinics, assisting in GP practices, and triaging in Emergency Departments (EDs) [6,7]. In Norwich Medical School in the UK, for example, after the announcement of closure, including cancellation of clinical placements, medical students were recruited in areas of greatest clinical need in order to assist with tasks such as basic nursing care, proning, and swab testing with significant benefits to both students and clinical teams [8].…”
Section: Engaging Students In Inpatient Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, as access to PPE and supervision improve, their contribution could be restricted to low-acuity COVID-19 patients [3]. This includes working in screening and assessment clinics, assisting in GP practices, and triaging in Emergency Departments (EDs) [6,7]. In Norwich Medical School in the UK, for example, after the announcement of closure, including cancellation of clinical placements, medical students were recruited in areas of greatest clinical need in order to assist with tasks such as basic nursing care, proning, and swab testing with significant benefits to both students and clinical teams [8].…”
Section: Engaging Students In Inpatient Activitiesmentioning
confidence: 99%
“…In primary care activities, medical students could take a variety of responsibilities. One possibility is to help patient temperature and saturation screening or take swabs and implement rapid testing that informs community surveillance [7,11]. It has been suggested that 'they can monitor patients with mild COVID-19 symptoms who are not admitted; expedite care for admitted patients by reviewing charts, drafting notes, and ensuring tests are performed; and follow-up with patients after discharge' [9].…”
Section: Engaging Students In Primary Care Activitiesmentioning
confidence: 99%
See 1 more Smart Citation